Commentary: Chronic SSRI stimulation of astrocytic 5-HT2B receptors change multiple gene expressions/editings and metabolism of glutamate, glucose and glycogen: a potential paradigm shift - Banas, Sophie (2015)
A commentary on Chronic SSRI stimulation of astrocytic 5-HT2B receptors change multiple gene expressions/editings and metabolism of glutamate, glucose and glycogen: a potential paradigm shift by Hertz, L., Rothman, D. L., Li, B., and Peng, L. (2015). Front. Behav. Neurosci. 9:25. doi: 10.3389/fnbeh.2015.00025